Balancing Privacy and Data Utility in Electronic Health Records: A Two-Stage Synthetic Data Generation Approach - Chadalawada, Priyatham; Bukaita, Dr. Wisam (Medical Research Archives, 2025)
Electronic Healthcare Records (EHR) data are essential for improving medical research, advancing patient care, and developing predictive healthcare models. However, the sensitive nature of EHR data raises significant privacy concerns, that require multiple protective layers and mechanisms before allowing the utilization of this data and conducting any analysis. Traditional differential privacy techniques, while effective in safeguarding patient information, often introduce unreasonable noise that compromises data utility. To address this challenge, this study presents a composite method that balances privacy protection with data quality. The process introduced in this study involves applying random noise as an interval-based perturbation technique by randomly adjusting data points within a predefined range to construct controlled variability which maintains its statistical integrity while allaying the risk of re-identification and Gaussian noise is added to enhance privacy protection further for preserving the data differentially private. In the second stage, kNN (K-Nearest Neighbors) is used to generate fully synthetic datasets by modeling patterns among neighboring data points. This creates records that preserve the original dataset’s statistical properties and relational structures without retaining identifiable information. This Two-Stage approach ensures robust privacy while producing high-fidelity synthetic data suitable for complex analyses, such as predictive modeling and longitudinal studies. Looking forward, this method will enable secure data sharing across institutions, accelerate AI-driven healthcare innovations, and support privacy-conscious research, paving the way for a future where EHR data can be leveraged safely and effectively